2002
DOI: 10.1074/jbc.m207369200
|View full text |Cite
|
Sign up to set email alerts
|

The Lectin Domain of UDP-GalNAc:Polypeptide N-Acetylgalactosaminyltransferase 1 Is Involved in O-Glycosylation of a Polypeptide with Multiple Acceptor Sites

Abstract: Mucin type O-glycosylation begins with the transfer of GalNAc to serine and threonine residues on proteins by a family of UDP-GalNAc:polypeptide N-acetylgalactosaminlytransferases. These enzymes all contain a lectin-like (QXW) 3 repeat sequence at the C terminus that consists of three tandem repeats (␣, ␤, and ␥). The putative lectin domain of one of the most ubiquitous isozymes, GalNAc-T1, is reportedly not functional. In this report, we have reevaluated the role of the GalNAc-T1 lectin domain. Deletion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 50 publications
(96 reference statements)
3
33
1
Order By: Relevance
“…We did not find detectable differences using time course analysis that enables monitoring rate of incorporation of multiple GalNAc residues (Table II). The γ-domain of the GalNAc-T1 lectin domain was previously shown not to be important for the enzyme in vitro activity, while both the α and β domains were required for extensive glycosylation of an apomucin substrate assumed to include the GalNAc-glycopeptide activity function of the enzyme (Tenno et al 2002). Regardless of the minor discrepancies in these results, it appears that the GalNAc-T13 Ex10b variant with its alternative γ-domain does not have major functional consequences.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…We did not find detectable differences using time course analysis that enables monitoring rate of incorporation of multiple GalNAc residues (Table II). The γ-domain of the GalNAc-T1 lectin domain was previously shown not to be important for the enzyme in vitro activity, while both the α and β domains were required for extensive glycosylation of an apomucin substrate assumed to include the GalNAc-glycopeptide activity function of the enzyme (Tenno et al 2002). Regardless of the minor discrepancies in these results, it appears that the GalNAc-T13 Ex10b variant with its alternative γ-domain does not have major functional consequences.…”
Section: Discussioncontrasting
confidence: 42%
“…This was clearly observed with the ΔEx9 variant which could not be expressed in insect cells as a secreted protein, whereas the Δ39Ex9 variant was secreted but had no detectable activity with the studied peptides. This may not be surprising, given the previous report that deletions in the γ, βγ or αβγ subdomains or point mutations that affect cysteines and disulphide bond formations in rat GalNAc-T1 give rise to non-functional enzymes (Tenno et al 2002). Nevertheless, it is important to make it clear that in other cases, GalNAc-Ts were effectively expressed without their lectin domains and they still retained their catalytic activity, at least with peptides Raman et al 2008).…”
Section: Discussionmentioning
confidence: 86%
“…All cDNA fragments thus obtained were mixed together and ligated by T4 ligase (Promega), obtaining pFastFHGP67 that codes for the GP67 secretion signal and the FLAG/His tags. Human pt-GalNAc-T cDNA deleted of the sequence for the cytosolic domain and the transmembrane region was prepared as outlined previously, 21) and inserted into the NotI and XbaI sites of pFastFHGP67. The isolated clone was used for transformation of the host strain E. coli DH10Bac TM .…”
mentioning
confidence: 99%
“…This raises the possibility that this isozyme has altered lectin activity. It is reported that the GalNAc-transferases have distinct manners of substrate recognition [33][34][35] ; one is based on protein-protein interaction, so-called the initial activity, and is involved in the glycosylation of non-glycosylated peptides, and the other requires the prior addition of GalNAc to peptide substrates to transfer more GalNAc residues to the substrates. The latter activity, called follow-up activity, is based on the recognition of GalNAc residues on the acceptor substrate by the lectin domain of the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Mutational studies on the rat GalNAc-T1 lectin domain identified an asparagine residue (Asp444) in the a repeat predominantly involved in the lectin activity. 34) In dGalNAc-T3, this residue is replaced with arginine. Thus, together with the aberrant insertions, the lectin domain of this isozyme may not be fully functional.…”
Section: Resultsmentioning
confidence: 99%